IMPLEMENTASI APPRECIATE ACHIEVEMENT UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MAN 01 KOTA MALANG - Annisa’ Miftahul Jannah; AzhaR Haq; Abdul Jalil (VICRATINA, 2019)
This study aims to find out how educators apply Appreciate Achievement along with their advantages and disadvantages along with solutions to improve student learning motivation in the subjects of Aqidah Akhlak (Case Study of MAN 01 Malang City). The problem faced is that there are some students who are bored with the Akidah Akhlak lessons because of the many subject matter that must be read. Data sources were obtained through interviews with several students. This study uses qualitative methods obtained through observation, interviews and documentation. Which is analyzed by data reduction, data analysis and drawing conclusions. The results of this study are that the teacher uses a number of steps when starting teaching using the Appreciate Achievement and the advantages of applying the value of character education, one of which is students look enthusiastic to take lessons and one of the disadvantages is there are still students who lack confidence in expressing opinions so that the solution given by educators in addressing one of the shortcomings is that educators randomly designate students to answer questions given by educators.